1996
DOI: 10.1159/000264313
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 in Pregnancy

Abstract: Our objectives were to assess the plasma coenzyme Q10 (CoQ10) levels in normal pregnancy, in pregnancy with a spontaneous contractile event, in spontaneous abortion and in threatened abortion. Six hundred and fifteen CoQ10 levels were analyzed in 483 pregnant women: 350 patients were employed to design a normal curve; 66 patients with spontaneous contractile activity underwent two or more CoQ10 analyses in different trimesters; 49 patients presented spontaneous abortion, and 18 patients threatened abortion. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 9 publications
3
21
0
Order By: Relevance
“…Supplementation with vitamins E and C in women at risk of preeclampsia showed significant beneficial effects [11]. Despite its clinical importance, little has been reported concerning the lipid-soluble antioxidant coenzyme Q 10 in complicated pregnancy [12].…”
Section: Introductionmentioning
confidence: 99%
“…Supplementation with vitamins E and C in women at risk of preeclampsia showed significant beneficial effects [11]. Despite its clinical importance, little has been reported concerning the lipid-soluble antioxidant coenzyme Q 10 in complicated pregnancy [12].…”
Section: Introductionmentioning
confidence: 99%
“…Increase of CoQ 10 during normal pregnancy most likely depends on the increase in LDL, which is the main carrier of CoQ 10 in plasma [26] and the increase in cholesterol level which is the biosynthetic pathway for CoQ 10 [27].Decrease of CoQ 10 during pre-eclampsia is due to direct reaction with free NO in reversible manner resulting in inhibition of mitochondrial complex I activity [26]. GĂŒrkan and Bozdag-DĂŒndar [28] stated that CoQ 10 reduces blood viscosity and improves blood flow thus reducing the systolic and diastolic pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors [21][22][23][24][25][26] have reported improved clinical conditions induced by CoQ10 in heart diseases and muscular pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…As we previously reported in 350 patients with normal pregnancy, the mean CoQ10 plasma level was 0.61 B 0. 16 [26][27][28][29][30]. The difference from fetal plasmatic behavior is evident: in the fetus the CoQ10 concentration does not increase with increasing gestational age.…”
Section: Discussionmentioning
confidence: 99%